Plato's Apology of Socrates : a literary and philosophical study with a running commentary - Strycker, E. de 1907-1978. (Mnemosyne, Supplements, 1994)
There have been many recent studies on the Apology . This book differs from them in that it attempts a synthesis of philosophical and literary approaches. A great deal of attention is paid to the philosophical and religious views that are present-often implicitly-in the text; they are much closer to the philosophy of Plato's main works than is usually assumed. But the Apology is also analysed as a rhetorical text: its close relationship with fourth-century rhetorical theory and practice is highlighted. The analyses of the various parts of the speech are followed by a detailed line-by-line commentary. The work was started by E. de Strycker, S.J.; after his death, it was revised and completed by S.R. Slings.